Peranan Media Sosial Instagram terhadap Interaksi Sosial dan Etika pada Generasi Z - Kartini Sikumbang; Widya Ramadhina; Emi Riska Yani; Della Arika; Nazmi Hayati; Nur Aini Hasibuan; Bagus Gigih Permana (Departement of Mathematics Education, 2024)
Instagram is a popular social media platform and is used by many people, including generation Z. This platform offers various features that support users in spreading content, interacting with friends, and building social networks. In recent years, Instagram has become a very popular platform among generation Z. This platform offers various interesting features, such as short video displays (IGTV), various content formats (carousel, album, and hybrid video), and interactive features such as stories and interactions with friends (likes, comments and shares). Therefore, Instagram is an ideal place for young people to interact socially and promises interesting content. This platform allows users to display their content creatively and interact with friends, either directly directing friends through comments and likes, or through the interactive feature Instagram Stories. In this context, we will discuss how Instagram's features influence the way generation Z interacts socially, as well as how this platform has become an important tool in their daily lives. Additionally, we'll discuss how users can optimize their Instagram experience to increase social interactions and build a strong network. In the results of this research, we will discuss the use of Instagram by generation Z in various aspects, from the features used to successful marketing strategies. By understanding the role of social media Instagram in social interaction in generation Z, we can conclude that Instagram has the potential to become a very important tool in the life and rise of generation Z in the digital world.